THE EFFECT OF HALAL CERTIFICATION AND BUNDLING STRATEGY ON PURCHASING DECISIONS THROUGH BUYING INTEREST AS AN INTERVENING VARIABLE - Vani Silviana; Rosana Eri Puspita (Universitas Islam Negeri Sumatera Utara Medan, 2025)
The phenomenon in the world of business is currently developing very rapidly. Indonesia's rapid economic growth and awareness of the importance of caring for oneself are great business opportunities for the beauty industry. Business actors in the beauty sector need to take advantage of this opportunity by presenting quality products that meet the needs of the Indonesian people. Because Indonesia is a country with high population growth, Indonesia can be a business opportunity for various types of beauty products, including skincare products and cosmetics. This study aims to determine the Effect of the Halal Certificate and Bundling Strategy on Consumer Decisions with Buying Interest Purchase Decisions as an Intervening Variable on consumers of Implora products in Boyolali Regency. This study uses a quantitative method. With the number of women in Boyolali Regency, especially those aged 15 to >40 years, as many as 156,211 people. Sampling uses the purposive sampling technique, in which 100 respondents are sampled from the entire population. In data processing, SPSS version 26 is used. The data analysis in this study uses instrument tests, classical assumption tests, hypothesis tests, path analysis, and Sobel tests. The results of the study show that partially.